Desafios do empreendedorismo digital no município de São Paulo de Olivença - AM - Batalha, Marcus Vinícius Moraes (Brasil, 2023)
World society has gone through a very delicate moment with regard to the COVID-19 pandemic, in addition, it has led to a large part of commercialization in an unpleasant decline, either partially or totally devastating. As a result, digital entrepreneurship, in this context, began to gain more visibility as a tool for restructuring the financial life of any individual, thus being a rejuvenating and valuable process for anyone who invests in something. In this way, the study aims to relate the marketing strategies developed by digital entrepreneurs with the impacts affected by the pandemic in the municipality of São Paulo de Olivença, Amazonas State, Brazil. For this purpose, an exploratory research of a qualitative nature was used as a methodology, with data collection through a semi-structured questionnaire. As a result, there was a predominance of the self-declared female gender in terms of quantity, greater age longevity, higher approximate average annual revenues by gender in relation to males and differentiated strategies in relation to those experienced by digital entrepreneurs. At the end of the research, it was possible to consider that digital entrepreneurship is a very challenging market and that, in this research site, it was demonstrated that women have a greater capacity to develop entrepreneurship in the digital field than men.